(untitled) (Revista Científica UCOM Scientia, 2025)
This study addresses the fragmentation of data on academic offerings and graduation in health careers in Paraguay, a problem stemming from a lack of unified standards and dispersed official information. The goal was to descriptively analyze these offerings and graduation rates using Data Analytics on open education system data. Methodologically, a quantitative, non-experimental approach was used, analyzing secondary data from the National Registry of Careers (RNC) and the National Registry of Higher Education Degrees (RTES). A processing pipeline was implemented, including data download, preparation, health-specific filtering, thematic grouping, gender inference, institutional management type inclusion, formatting cleanup, and pivot table analysis. The results reveal a healthcare training system characterized by significant privatization (89.2% of degrees) and marked feminization (75.7% of female graduates). Geographically, offerings are concentrated in three departments (49.1%). Nursing predominates (36.9% of degrees) over medicine (20.6%), with 2.3 nurses for every doctor. The analysis also showed important institutional disparities, such as the Juan Pablo II Superior Institute of Health Sciences, which leads in offerings but has modest graduate production. Universities are central, granting 73.9% of degrees despite being only 39.3% of institutions. These findings provide critical information for educational policy and health human resource planning.